(untitled) (Bulletin of Kharkiv National University of Internal Affairs, 2025)
The article emphasises that criminal offences against justice committed by professional participants in justice are characterised by a specific intent, which is to violate the principles of justice, undermine confidence in law enforcement agencies and the judicial system, and also to cause harm to both victims and society as a whole. Given these features, it is substantiated that the development of methods for investigating such offences is one of the main tasks on the way to counteracting these facts of criminal behaviour. Based on the generalisation of scholars’ approaches, it is additionally argued that forensic characterisation is a mandatory substantive component of a separate methodology for investigating criminal offences. Given some differences in the mechanism of criminal unlawful activity, the crimes and criminal misdemeanours under study are divided into three subgroups, and then the components of the mechanism are studied for each subgroup. According to the results of the analysis of specific features of the type mechanism of criminal unlawful activity, the structure of forensic characteristics of criminal offences against justice committed by its professional participants is determined. It is found that its substantive elements can be classified into two groups: basic and additional (optional). The basic elements of the forensic characteristics of criminal offences of the type under study include: the method of commission, the circumstances of commission, including place and time; traces of criminal activity; identity of the offender and identity of the victim. The optional elements (which are not always reflected in the mechanism of criminal activity) are the instruments and means of committing criminal offences, as well as the motives and objectives of criminal behaviour. Prospects for further research are identified in a thorough understanding of each of the identified elements of the structure of the forensic characteristic.